2019
DOI: 10.1177/1090198119889098
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Health Promotion in Sports Club Settings: A Modified Delphi Study

Abstract: Settings-based approaches have become an increasing health promotion focus since the World Health Organization’s 1986 Ottawa Charter. While schools, cities, and prisons have implemented this approach, its development within sports environments is recent. Sports are a popular leisure-time activity, requiring validated tools to measure health promotion activity. This study’s aim was to develop a measurement tool based on international consensus that measures perceptions of health promotion within sports clubs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…This approach has been used in settings like schools, prisons, universities [ 47 , 48 , 49 ] and, from the early 2000s, also in sports clubs [ 50 ]. The theoretical basis for health-promoting sports club (HPSC) research has been thoroughly developed in recent years [ 51 , 52 , 53 ]. A HPSC can be described as a sports club that views all its activities through the lens of health promotion, including all club actions beyond promoting one single health behavior (like for ex.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used in settings like schools, prisons, universities [ 47 , 48 , 49 ] and, from the early 2000s, also in sports clubs [ 50 ]. The theoretical basis for health-promoting sports club (HPSC) research has been thoroughly developed in recent years [ 51 , 52 , 53 ]. A HPSC can be described as a sports club that views all its activities through the lens of health promotion, including all club actions beyond promoting one single health behavior (like for ex.…”
Section: Introductionmentioning
confidence: 99%
“…This work adds empirical findings on the outcomes of coaches' health promotion activities across the lifespan, reinforcing the rationale that these activities are beneficial not only to youth but also to adult sports experiences and health. Moreover, these results emphasise the role sports clubs can play in public health (Honta, 2016), not only by increasing physical activity (Kokko et al, 2019) but also by embracing the settings-based approach (Kokko, 2014b) to consider sports participants' health in a holistic way (Geidne et al, 2019;Johnson et al, 2019). As this research demonstrated, coaches' health promotion activities should be tailored to participant age, gender and type of sports in order to produce the greatest perceived benefits.…”
Section: Resultsmentioning
confidence: 71%
“…A feeling of social responsibility, including a focus on inactive people, and the acknowledgment of the multiple benefits of the program for the club, stimulated macro-level activities. In a recent study, experts in the fields of sport and health defined the determinants of a health-promoting sports club more precisely [ 39 ]. The factors found in our study resemble some of these determinants, such as “my sports club offers sports for people who are inactive or sedentary” (cultural determinant, macro-level vs. a focus on inactive people); and “officials of my sports club allocate resources to health promotion” (economic determinant, meso-level vs. availability of human resources).…”
Section: Discussionmentioning
confidence: 99%